Diagnostic Performance of Magnetic Resonance Imaging for Vertebral Metastases in Routine Clinical Practice: MRI Diagnostic Performance for Vertebral Metastases in Routine Practice - Khan, Laila; Orakzai, Zubair Janan; Begum, Tabassum; Baig, Hina; Noureen, Sumaira; Sadiq, Muhammad (Pakistan Journal of Health Sciences, 2026)
Vertebral metastasis is a frequent complication of systemic malignancies and may cause pain, pathological fractures, and neurological compromise. MRI is commonly used for suspected spinal metastases; however, the diagnostic performance of routine 1.5-Tesla MRI interpreted using visual criteria in everyday practice remains unclear. Objectives: To determine the diagnostic accuracy of conventional MRI for the detection of vertebral metastases using histopathology and/or multidisciplinary clinic radiologic consensus as reference standards. Methods: This prospective cross-sectional study at MTI Bacha Khan Medical College and Mardan Medical Complex, Pakistan (15 Sept–15 Dec 2025), included 106 adults with suspected vertebral neoplastic lesions who underwent 1.5-Tesla MRI. Two blinded radiologists independently interpreted scans, resolving discrepancies by consensus. Histopathology and/or tumor board consensus served as the reference standard. Sensitivity, specificity, predictive values, accuracy, and ROC-AUC were calculated. Results: Of 106 patients, 64 (60.4%) had vertebral metastases by the reference standard. MRI sensitivity was 42.2% (95% CI: 30.1–54.3), specificity 54.8% (95% CI: 39.7–69.9), PPV 58.7% (95% CI: 44.5–72.9), NPV 38.3% (95% CI: 26.1–50.5), and overall accuracy 47.2% (95% CI: 37.7–56.7). The AUC was 0.515 (95% CI: 0.40–0.63). False positives were commonly due to hemangioma and infection, whereas false negatives were mainly related to poor image quality, small/early lesions, and reader variability. Conclusions: Conventional 1.5-Tesla MRI using routine visual criteria showed low sensitivity, modest specificity, and limited accuracy for vertebral metastases. Clinical correlation and reference-standard confirmation remain essential for equivocal cases.